Pemberian bimbingan belajar Bahasa Inggris Bagi Siswa Sekolah Dasar di Desa Ridan Permai Kecamatan Bangkinang Kota - Yetti , Dzulhijjah; Rahmad Akbar; Nofiar.Am, Andri; Pribadi, Antoni; Habibie, Indra; Nurkholis; Febrianton, Adi; Kurniaty, Tri (Politeknik Kampar, 2024)
This Community Service Program aims to provide English tutoring for elementary school students in Ridan Permai Village, Bangkinang Kota District. The program is designed to help students master basic English skills, considering the low level of English proficiency among students in the village. Additionally, the lack of interest in learning English outside school hours presents a challenge that needs to be addressed. Through this program, it is hoped that students will develop awareness to study independently at home and improve their English skills, including listening, reading, speaking, and writing, as well as mastery of grammar and vocabulary. Evaluation results indicate a significant improvement in the students' English proficiency, with an attendance rate of 100%. It is hoped that this program will be sustainable and continued by the local community after the program ends.